GPR15–C10ORF99 functional pairing initiates colonic Treg homing in amniotes. (23rd December 2021) - Song, Jingjing; Zheng, Huaping; Xue, Jingwen; Liu, Jian; Sun, Qian; Yang, Wei; Liu, Fang; Xiang, Xiangyin; He, Kai; Chen, Younan; Cheng, Jingqiu; Li, Wei; et al.
Abstract: Regulatory T lymphocyte (Treg) homing reactions mediated by G protein‐coupled receptor (GPCR)–ligand interactions play a central role in maintaining intestinal immune homeostasis by restraining inappropriate immune responses in the gastrointestinal tract. However, the origin of Treg homing to the colon remains mysterious. Here, we report that the C10ORF99 peptide (also known as CPR15L and AP57), a cognate ligand of GPR15 that controls Treg homing to the colon, originates from a duplication of the flanking CDHR1 gene and is functionally paired with GPR15 in amniotes. Evolutionary analysis and experimental data indicate that the GPR15–C10ORF99 pair is functionally conserved to mediate colonic Treg homing in amniotes and their expression patterns are positively correlated with herbivore diet in the colon. With the first herbivorous diet in early amniotes, a new biological process (herbivorous diet short‐chain fatty acid‐C10ORF99/GPR15‐induced Treg homing colon immune homeostasis) emerged, and we propose an evolutionary model whereby GPR15–C10ORF99 functional pairing has initiated the first colonic Treg homing reaction in amniotes. Our findings also highlight that GPCR–ligand pairing leads to physiological adaptation during vertebrate evolution. SYNOPSIS: The GPR15–C10ORF99 pair is functionally conserved to mediate colonic Treg homing in amniotes. Their expression patterns are positively correlated with herbivore diet, suggesting that this functional pairing initiates the first colonic Treg homing reaction in amniotes. C10ORF99 originated via duplication of the flanking CDHR1 gene and is functionally paired with GPR15 in amniotes. The GPR15–C10ORF99 pair is functionally conserved to mediate the first colonic Treg homing reaction in amniotes. GPR15–C10ORF99 expression patterns in the colon correlate with an herbivore diet in amniotes. Abstract : The GPR15–C10ORF99 pair is functionally conserved to mediate colonic Treg homing in amniotes. Their expression patterns are positively correlated with herbivore diet, suggesting that this functional pairing initiates the first colonic Treg homing reaction in amniotes.